Retrospective case analysis of antiviral therapies for HHV‐6 encephalitis after hematopoietic stem cell transplantation. Issue 1 (1st September 2020) - Toomey, Danny; Phan, Tuan L.; Nguyen, Vanessa; Phan, Thommas T.; Ogata, Masao
Abstract: Human herpesvirus 6 (HHV‐6) is one of the most common causes of encephalitis in allogeneic hematopoietic stem cell transplant (HCT) recipients and is associated with significant morbidity and mortality. There are no FDA‐approved treatments specifically for HHV‐6 encephalitis; HHV‐6 disease is typically treated with CMV antivirals. A review of antiviral medications used to treat HHV‐6 encephalitis was conducted by aggregating data from case reports found on PubMed. Articles were included if they examined at least one HCT patient diagnosed with HHV‐6 encephalitis and described their treatment course and outcome. Key data were abstracted from 123 cases described in 52 studies. The proportion of patients with encephalitis who died or developed sequelae was 63.6% among ganciclovir monotherapy recipients (n = 44), 55.3% among foscarnet monotherapy recipients (n = 47), and 37.5% among recipients of combination therapy with foscarnet and ganciclovir (n = 32). Logistic regression revealed that recipients of foscarnet (OR 4.286, 95% CI 1.235‐14.877, P  = .022) and ganciclovir (OR 5.625, 95% CI 1.584‐19.975, P  = .008) monotherapies were more likely to develop sequelae compared to recipients of combination therapy, respectively. In multivariate analyses, non‐cord blood transplant was identified as an independent risk factor for developing sequelae after receiving ganciclovir monotherapy (OR 5.999, 95% CI 1.274‐28.254, P  = .023). There was no difference in mortality between patients who received combination therapy and those who received monotherapy. In conclusion, combination therapy with foscarnet and ganciclovir may reduce sequelae, but not mortality, secondary to HHV‐6 encephalitis.